Seizure and Pulmonary Embolism: A Differential That Can Save a Life - Seyedmohammad Pourshahid; Sneha Dedhia; Shakeeb Hakim; Mohamed Barakat; Dennis Genin (Case Reports in Pulmonology)
Seizures is a relatively common presentation with a wide differential diagnosis. However, seizures presenting secondary to underlying pulmonary emboli are rare and, without prompt recognition and management, this easily treatable condition can be potentially fatal. The few available case reports discussing seizures and PE reveal a high mortality rate which underscores the importance of prompt diagnosis. A 38-year-old woman presented to the emergency room having experienced loss of consciousness and a generalized tonic-clonic seizure at home. In the emergency room, her presenting signs and symptoms included tachycardia, worsening dyspnea, mild hypoxemia, and elevated D-dimer. Pertinent history findings revealed she recently received depot hormonal contraceptive treatments. Her initial workup included an EKG which showed sinus tachycardia without evidence of right heart strain. Subsequently a chest CT with angiography revealed massive bilateral pulmonary emboli. DVT studies also revealed a unilateral acute DVT. The patient was promptly started on therapeutic anticoagulation and stabilized. Fortunately, the patient remained symptom-free and eventually was discharged with close follow-up. The goal of this report is to make clinicians more aware of the possibility that seizures, along with the appropriate clinical findings, can be caused by acute PE.